A randomized controlled trial of a multicomponent online stress reduction intervention in inflammatory bowel disease. (September 2022) - Peerani, Farhad; Watt, Makayla; Ismond, Kathleen P; Whitlock, Reid; Ambrosio, Lindsy; Hotte, Naomi; Mitchell, Nicholas; Bailey, Robert J; Kroeker, Karen; Dieleman, Levinus A; Siffledeen, Jesse; Lim, Allen; et al.
Background: Psychological stress negatively impacts inflammatory bowel disease (IBD) outcomes. Patients have prioritized access to online interventions; yet, the data on these have been limited by mixed in-person/online interventions, low adherence, and non-randomized controlled trial (RCT) design. Objectives: We assessed the efficacy of and adherence to a 12-week online multicomponent stress reduction intervention in IBD. Design: This is a RCT. Methods: Adult participants on stable IBD medical therapy with elevated stress levels from four centers were randomized to intervention or control groups. Intervention participants received a 12-week online program including a weekly yoga, breathwork and meditation video (target 2–3 times/week), a weekly cognitive behavioral therapy/positive psychology informed video activity, and weekly 10-min check-ins by a study team member. Control participants received weekly motivational messages by email. All patients received standard of care IBD therapy. The primary outcome was Cohen's Perceived Stress Scale (PSS). Secondary outcomes evaluated mental health, resilience, health-related quality of life (HRQoL), symptom indices, acceptability, adherence, and inflammatory biomarkers. Analysis of covariance was used to determine between-group differences. Results: Of 150 screened patients, 101 were randomized to the intervention ( n  = 49) and control ( n  = 52) groups (mean age: 42.5 ± 14.1 years; M:F 1:3, 48% with ulcerative colitis and 52% with Crohn's disease). The between-group PSS improved by 22.4% (95% confidence interval, 10.5–34.3, p  < 0.001). Significant improvements were seen in mental health, resilience, and HRQoL measures, with a median satisfaction score of 89/100 at the end of the 12 weeks. In the 44/49 patients who completed the intervention, 91% achieved program adherence targets. Conclusion: This 12-week online intervention improved perceived stress, mental health, and HRQoL, but did not impact IBD symptom indices or inflammatory biomarkers. The program was readily adopted and adhered to by participants with high retention rates. After iterative refinement based on participant feedback, future studies will evaluate the impact of a longer/more intense intervention on disease course. Registration: ClinicalTrials.gov Identifier NCT03831750 Plain Language Summary: An online stress reduction intervention in inflammatory bowel disease patients improves stress, mental health, and quality of life People with inflammatory bowel disease (IBD) have high levels of stress, anxiety, and depression. Although IBD patients have expressed the need for online mental wellness interventions, the existing data to support these interventions in IBD are limited. In this trial, 101 IBD patients had the chance to participate in a 12-week online stress reduction intervention. In those patients randomly selected to participate in the online intervention, each week they received the following: a 20- to 30-min yoga, breathwork, and meditation video that they were asked to do 2–3 times a week, a 10- to 20-min mental wellness activity they were asked to do once during the week, and a 10-min telephone check-in with a study team member. Participants who were not selected to use the online intervention received a weekly motivational message by email. In all, 90 of the 101 participants (89%) completed the study with the mean age of participants being 43 years and the majority being females (75%). Ninety-one percent of participants who completed the intervention met the program target of doing the yoga, breathwork, and meditation video at least 2 times per week. Significant improvements were seen in perceived stress (by 22.4%), depression (by 29.5%), anxiety (by 23.7%), resilience (by 10.6%), and quality of life (by 8.9%). No changes were seen in IBD severity or in blood markers of inflammation. In conclusion, this study demonstrates evidence that a 12-week online stress reduction intervention had low dropout rates, high adherence and beneficial effects on stress, mental health, and quality of life measures. Continued feedback will be sought from study participants and our IBD patient partners to refine the intervention and assess the impact in future studies of patients with active IBD, as well as the impact of a longer/more intense intervention.